The Traditional Way of Saving Money Versus the Modern Style of Invest-ment: The Financial Management Styles of Sorsogon State University (Sor-su) Bulan Campus Faculty Members - Bongalonta, Michael B.; Bongalonta, Michelle M.; Gigantoca, Santos E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This research was conducted to identify the practices employed by the SorSU Faculty members towards saving money as well as discover the problems encountered by them in handling their finances. A total of 40 faculty members of Sorsogon State University Bulan Campus participated in this study. The mixed designed was used in this research which employed survey and focus group discussions. This study concludes that the faculty members of SorSU Bulan Campus adopt both the traditional way of saving money and the modern style of investment as modes of saving their finances which include budgeting, joining in “paluwagan”, using piggy bank, maintaining bank accounts and deposits and purchasing investment instruments. Increasing cost of utilities and unexpected day-to-day expenses; lack of financial literacy; poor debt management; and low and delayed salaries were the problems encountered by the faculty participants in handling their monetary resources. From the results of the study, this highly recommends the adoption of the Bongalonta’s Financial Model for SorSU Bulan Campus Faculty Members designed by the researcher as a guide or model for saving money. It is likewise recommended that seminars and trainings on financial literacy may be conducted.